The Diversity of Sequence and Chromosomal Distribution of New Transposable Element-Related Segments in the Rye Genome Revealed by FISH and Lineage Annotation - Zhang, Yingxin; Fan, Chengming; Li, Shuangshuang; Chen, Yuhong; Wang, Richard R.-C.; Zhang, Xiangqi; Han, Fangpu; Hu, Zanmin (Frontiers in Plant Science, 2017)
Transposable elements (TEs) in plant genomes exhibit a great variety of structure, sequence content and copy number, making them important drivers for species diversity and genome evolution. Even though a genome-wide statistic summary of TEs in rye has been obtained using high-throughput DNA sequencing technology, the accurate diversity of TEs in rye, as well as their chromosomal distribution and evolution, remains elusive due to the repetitive sequence assembling problems and the high dynamic and nested nature of TEs. In this study, using genomic plasmid library construction combined with dot-blot hybridization and fluorescence in situ hybridization (FISH) analysis, we successfully isolated 70 unique FISH-positive TE-related sequences including 47 rye genome specific ones: 30 showed homology or partial homology with previously FISH characterized sequences and 40 have not been characterized. Among the 70 sequences, 48 sequences carried Ty3/gypsy-derived segments, 7 sequences carried Ty1/copia-derived segments and 15 sequences carried segments homologous with multiple TE families. 26 TE lineages were found in the 70 sequences, and among these lineages, Wilma was found in sequences dispersed in all chromosome regions except telomeric positions; Abiba was found in sequences predominantly located at pericentromeric and centromeric positions; Wis, Carmilla and Inga were found in sequences displaying signals dispersed from distal regions toward pericentromeric positions; except DNA transposon lineages, all the other lineages were found in sequences displaying signals dispersed from proximal regions toward distal regions. A high percentage (21.4%) of chimeric sequences were identified in this study and their high abundance in rye genome suggested that new TEs might form through recombination and nested transposition. Our results also gave proofs that diverse TE lineages were arranged at centromeric and pericentromeric positions in rye, and lineages like Abiba might play a role in their structural organization and function. All these results might help in understanding the diversity and evolution of TEs in rye, as well as their driving forces in rye genome organization and evolution.